The Impact of COVID-19 Home Confinement on Mexican University Students: Emotions, Coping Strategies, and Self-Regulated Learning - Gaeta, Martha Leticia; Gaeta, Laura; Rodriguez, María del Socorro (Frontiers in Psychology, 2021)
One of the main challenges in higher education is promoting students' autonomous and self-regulated learning, which involves managing their own emotions and learning processes in different contexts and circumstances. Considering that remote online learning during COVID-19 lockdown can be an opportunity for university students to take greater responsibility for their learning, it will be essential to know the strategies they have developed in the face of emotional and learning challenges during this health crisis. This study aimed to analyze the impact of COVID-19 home confinement in university students on an emotional level, their coping strategies, and self-regulated learning in online learning. Participants were 1,290 Mexican students from different higher education institutions throughout the country. Students answered an online self-report questionnaire using standardized instruments adapted to the pandemic. Data were analyzed with descriptive, correlational, and linear regression analyses. Findings indicate that, although anxiety and frustration were present among participants during confinement, the primary emotions were gratitude and hope. The main coping strategies used by students were active, aimed at facing and reassessing the situation. Emotions such as tranquility, hope, gratitude, and joy were positively related to self-regulated learning, while loneliness and disinterest were negatively related. Coping strategies mediated the relationship between emotions and self-regulated learning. Thus, teachers should help students understand the relevance of active coping strategies and use student-centered learning models that promote autonomous and self-regulated learning, considering each learner's reality, during and after confinement.